IMPLIKASI AUKUS TERHADAP HUBUNGAN EKONOMI AUSTRALIA DAN TIONGKOK TAHUN 2021-2022 - Oktavianto, Fajar (Department of International Relations Universitas Satya Negara Indonesia, 2023)
This research analyzes economic relations between China and Australia after Australia joined defense technology cooperation AUKUS. The United States, United Kingdom, and Australia established AUKUS to contain China in Indo-Pacific, which is the center of world economics and geopolitics today. This research, therefore, aims to discuss the impact of AUKUS towards economic relations between China and Australia in 2021 and 2022. Using a qualitative research method and Kenneth Waltz’s neorealism theory and national interest concept, the author found that Australia's foreign policy to become AUKUS member worsened its economic relations with China. In 2021, China suspended the entry of import commodities from Australia to politically retaliate Australia. By banning Australia’s commodities, China not only sought to attack Australian trade, but also defended its national interests in state sovereignty, national security, and territorial integrity.